Antimicrobial activity of six plant extracts from the brazilian savanna on periodontal pathogens - Gaetti-Jardim Júnior, Elerson [UNESP]; Landucci, Luís Fernando; Arafat, Omar Khalil Kidudsi; Ranieri, Robson Varlei [UNESP]; Ramos, Marcelle Marie Buso [UNESP]; Ciesielski, Francisco Isaak Nícolas [UNESP]; Schweitzer, Chrisitane Marie [UNESP]; Okamoto, Ana Cláudia [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2011)
The extracts of plants from Brazilian savanna are currently used in popular medicine. This study evaluated the inhibitory activity of the alcoholic and aqueous extracts from savanna plants on periodontal bacteria. The minimal inhibitory concentrations were evaluated by the agar dilution method, using Wilkins-Chalgren agar. Antimicrobial activity of plants extracts on microbial biofilms was determined in microplates. Psidium cattleianum and Myracrodruon urundeuva extracts demonstrated significant inhibitory activity on all bacterial strains tested; alcoholic and aqueous extracts showed similar results. The extracts from these two species were able to inhibit both planktonic cells and microbial biofilm.

Los extractos de las plantas de la sabana brasileña actualmente se utilizan en la medicina popular. Este estudio evaluó la actividad inhibitoria de los extractos alcohólicos y acuosos de plantas de la sabana en bacterias periodontales. Las concentraciones inhibitorias mínimas fueron evaluados por el método de dilución en agar, utilizando agar Wilkins-Chalgren. La actividad antimicrobiana de los extractos de plantas en las biopelículas microbianas se determinó en microplacas. Los extractos de Psidium cattleianum y Myracrodruon urundeuva demostraron una importante actividad inhibitoria sobre todas las cepas bacterianas probadas, extractos alcohólicos y acuosos mostraron resultados similares. Los extractos de estas dos especies fueron capaces de inhibir las células planctónicas y biofilm microbiano.
Actividad antimicrobiana de seis extractos de plantas de la sabana brasileña en patógenos periodontales
Keywords: Anaerobic bacteria; Plant extracts; Antimicrobial agents; Periodontitis; Bacterias anaerobias; Extractos de plantas; Agentes antimicrobianos; Periodontitis